Prospects of the Use of Cell Therapy to Induce Immune Tolerance - Wang, Zhenkun; Liu, Xiaolong; Cao, Fenglin; Bellanti, Joseph A.; Zhou, Jin; Zheng, Song Guo (Frontiers in Immunology, 2020)
Autoimmune diseases (ADs) are a serious hazard to human health and well-being. As an alternative therapeutic approach, cell therapy, in which cellular material is injected or implanted into a patient, has the potential to overcome the limitations of traditional drug treatment and to alleviate the symptoms of many refractory diseases. The use of cell therapy has led to the development of new techniques and significantly contributed to the promise of inducing immune tolerance and restoring immunologic homeostasis. The purpose of this review is to describe the current panoramic scope of cell therapy in immunologically-mediated disorders, discuss the advantages and disadvantages of different types of cell therapy, and to explore novel directions and future prospects for these tolerogenic therapies.